Maternal Knowledge and Motivation in Preventing Stunting among Toddlers in Semarang or another shorter version - Rohmatal Izzah, Isqina; Ardian, Iwan (CV. Dyoqu Publishing Management, 2025)
Background:Stunting is a chronic nutritional problem that remains a serious challenge in Indonesia. This condition impacts physical growth, cognitive development, and the quality of future human resources. Mothers' knowledge and motivation in providing balanced nutrition are crucial factors that can influence the nutritional status of toddlers. Aims: This study aims to analyze the relationship between maternal knowledge about stunting and motivation to provide balanced nutrition to toddlers aged 7–24 months in the working area of ​​Bangetayu Community Health Center, Semarang City. Methods:The study used a descriptive, correlative design with a cross-sectional approach. The sample consisted of 115 mothers of toddlers selected using simple random sampling. The instrument was a structured questionnaire covering demographic data, knowledge about stunting, and motivation for providing balanced nutrition. Data analysis was performed using the Spearman Rank test. Result:The results showed that the majority of respondents had high levels of knowledge (73%) and strong motivation (53.9%). Spearman Rank correlation analysis yielded a coefficient of r = 0.744 with p < 0.05, indicating a very strong and significant relationship between maternal knowledge about stunting and motivation to provide balanced nutrition to toddlers. Conclusion:Maternal knowledge has been shown to play a crucial role in increasing motivation to provide balanced nutrition. Comprehensive and ongoing health education needs to be strengthened as a preventative measure to reduce the prevalence of stunting, particularly during a child's first 1,000 days of life.